HUBUNGAN ANTARA POLA ASUH ORANG TUA DENGAN KEMAMPUAN TOILET TRAINING ANAK USIA PRA SEKOLAH DI BANJAR KUTUH KELOD UBUD - Ni Kadek Win Oktaviari; Ni Luh Made Asri Dewi; Putu Susy N.A Astini; Kurniasih Widayati (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2018)
Background: Toilet training is an attempt to train children to be able to control bowel movements. In Indonesia, it was found that 16% of children aged 6 years were still unable to do toilet training independently. One of the important factors in the success of children in doing toilet training is the parenting style applied by parents in educating children at home. Objective: to find out the relationship between parenting style and toilet training ability in pre-school aged children in Kutuh Kelod Banjar Ubud. Method: This study used an observational analysis design with a cross sectional approach. The study population was pre-school age children in Banjar Kutuh Kelod Ubud with sampling techniques using purposive samling. The instrument of this study used the observation sheet toilet training ability and parenting questionnaire. Analysis of toilet training capabilities with parenting using the Spearmans Rho test. Results: The study showed that most of the parents' parenting styles were democratic as many as 24 people (40%). The results of the Spearmans Rho test were parenting and toilet training abilities with a value of p = 0,000. Conclusion: This study found that there was a significant relationship between parenting care and toilet training abilities of preschoolers.Keywords: Parenting; toilet training; pre-school children